MODEL REGRESI DATA PANEL DINAMIS DENGAN ESTIMASI PARAMETER ARELLANO-BOND PADA PERTUMBUHAN EKONOMI DI INDONESIA - Muhammad Emir Wicaksono; Di Asih I Maruddani; Iut Tri Utami (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2023)
Economic growth is one of factor for knowing rate of income in some country and knowing the rate of income from the indicator the value of Gross Domestic Product (GDP). The factor to be expected that affected GDP are Human Development Index (HDI), Foreign Investment, Domestic Investment, inflation, export net, Labour Participation Rate, and Government Spending. The research to determine a model and short-term effect also long-term effect from the variable that suspected to affect economic growth in Indonesia. The research does with dynamic panel data model defined as model involved lag from dependent variable as their independent variable. Usage of lag on the model caused of estimation with Ordinary Least Square (OLS) produced bias and inconsistent estimation. Generalized Method of Moment (GMM) Arellano-Bond estimation which is the parameter estimation with first differencing and instrumental variable method used to clear the solution of OLS produced bias and inconsistent estimation. The research produced model from variable influence to economic growth in Indonesia, HDI and Government Spending. Short-term effect from HDI for GDP has increased 2,410332 percent and long-term effect has increased 18,7610975 percent. Short-term effect from Government Spending for GDP has decreased 0,1025608 percent and long-term effect has decreased 0,798293831 percent.